On the possibility of rhenium clustering in nickel-based superalloys - Mottura, A; Finnis, M; Reed, R (2012)
In order to elucidate the role of this element in superalloy metallurgy, the binding energy of Re-Re pairs and the stability of small Re clusters in the nickel face-centred cubic (fcc) lattice is investigated using ab initio density functional theory. It is shown that the formation of Re-Re nearest neighbour pairs is energetically unfavourable, and that this repulsive energy is dramatically reduced as soon as the solute atoms move further apart from one another. Furthermore, small nearest neighbour and second neighbour Re clusters are found to be unstable. The calculations are repeated for W and Ta, which lie beside Re in the periodic table; the results are essentially the same, except that some Ta-Ta higher order pairs have a positive binding energy, consistent with the Ni-Ta binary phase diagram exhibiting several ordered intermetallics. The predictions show that Re clusters are unstable in fcc Ni and it is unlikely that clustering has a role in improving creep and fatigue properties (the rhenium-effect) in Ni-based superalloys. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.